Development of E-Modules Based on Project Based Learning (PjBL) on Periodic System of Elements Material - Sinaga, Bunga Apriani; Purba, Jamalum (Universitas Lampung, 2024)
This research was conducted in November 2023-February 2024 at SMAN 1 Percut Sei Tuan with the aim of finding out: (1) the feasibility of e- learning modules based on Project Based Learning (PjBL) on periodic system of elements material based on the BSNP assessment instrument consisting of content feasibility, appropriateness of presentation, appropriateness of language and appropriateness of graphics, (2) practicality of e- learning modules based on Project Based Learning (PjBL) on material on the periodic system of elements through responses from chemistry teachers and students. This research was carried out with Research and Development (Research and Development ) using the 4D development model ( define, design, develop, disseminate) which is limited to the develop stage . The initial stages carried out in this research were initial analysis, ATP analysis, and analysis of teaching materials. Then the design and creation of e- learning modules based on Project Based Learning (PjBL) were carried out on the material of the periodic system of elements. The final result of the e- module is converted into a flipbook with the help of the Flip PDF Professional application . Then the e-module was validated for its suitability by 6 validators. After carrying out the feasibility validation stage and the revision or improvement stage, a practicality test was carried out through the responses of 2 chemistry teachers and 31 students. The results of the e- module feasibility percentage obtained in the research were content feasibility of 94%, presentation feasibility of 95%, language feasibility of 96%, and graphic feasibility of 85%, where the four assessments were included in the